Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Pelanggan Di Kedai Pak Miko Kediri Tahun 2026 - Machsun Machsun; Ilyas Indra; Dika Zaim Adlhan (Excellent, 2026)
The purpose of this study is to analyze the influence of product quality, service quality, and price on customer loyalty at Kedai Pak Miko Kediri. This study employs an observational design with a cross-sectional approach. The sampling technique used is accidental sampling. The population of this study consists of all customers of Pak Miko's shop in Kediri. The sample comprises 96 respondents. The independent variables are product quality, service quality, and price, while the dependent variable is customer loyalty. Statistical data analysis was conducted using a logistic regression test. The results of this study indicate that product quality influences customer loyalty at Kedai Pak Miko Kediri (0.010), service quality influences customer loyalty at Kedai Pak Miko Kediri (0.009), and price influences customer loyalty at Kedai Pak Miko Kediri (0.001).Product quality, service quality, and price influence customer loyalty at Kedai Pak Miko Kediri.